2010
DOI: 10.1095/biolreprod.109.081729
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of Platelet-Derived Growth Factor and Estrogen-Signaling Pathways in Inducing Neonatal Rat Testicular Gonocytes Proliferation1

Abstract: We previously found that platelet-derived growth factor (PDGF) and 17beta-estradiol stimulate gonocyte proliferation in a dose-dependent, nonadditive manner. In the present study, we report that gonocytes express RAF1, MAP2K1, and MAPK1/3. Inhibition of RAF1 and MAP2K1/2, but not phosphoinositide-3-kinase, blocked PDGF-induced proliferation. AG-370, an inhibitor of PDGF receptor kinase activity, suppressed not only PDGF-induced proliferation but also that induced by 17beta-estradiol. In addition, RAF1 and MAP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 67 publications
2
49
1
2
Order By: Relevance
“…However, in the same study, RA was reported to slightly increase PND3 gonocyte numbers and have no effect on apoptosis. Moreover, activin A and androgen were reported to be negative regulators of fetal gonocyte proliferation, whereas we did not find any effect of testosterone on PND3 gonocyte proliferation in vitro (Merlet et al 2007, Thuillier et al 2010, Mendis et al 2011.…”
Section: Introductioncontrasting
confidence: 90%
See 2 more Smart Citations
“…However, in the same study, RA was reported to slightly increase PND3 gonocyte numbers and have no effect on apoptosis. Moreover, activin A and androgen were reported to be negative regulators of fetal gonocyte proliferation, whereas we did not find any effect of testosterone on PND3 gonocyte proliferation in vitro (Merlet et al 2007, Thuillier et al 2010, Mendis et al 2011.…”
Section: Introductioncontrasting
confidence: 90%
“…This transdifferentiation requires activation of the ERK1/2 and Smad2/3 signaling pathways (Zhang et al 2013b). Interestingly, we have previously shown that ERK1/2 activation is necessary for gonocyte proliferation, but that it does not participate in gonocyte differentiation R148 G Manku and M Culty (Thuillier et al 2010, Manku et al 2014. The ability of SSCs to transdifferentiate into mature hepatocytes is quite remarkable, illustrating the high plasticity of these unipotent stem cells, capable of reverting to pluripotency under specific conditions, representing potential clinical use in the treatment of liver diseases (Zhang et al 2013b).…”
Section: Ra-induced Decreases In Mirc1 and Mirc3 In Thy1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, their direct influence cannot be ruled out and this has been postulated in studies by other authors. Estrogens stimulate proliferation of gonocytes [44,45], increase the number of spermatogonia A [46], and stimulate DNA synthesis in spermatogonia in the rat [47]. In human testis tissue cultures, estradiol has been shown to act as a germ cell survival factor [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gonocytes express RAF1 (v-rafleukemia viral oncogene 1), MAP2K1 (mitogen-activated protein kinase kinase 1), and MAPK1/3 (mitogen-activated protein kinase 1/3). Thuillier and colleagues reported that inhibiting RAF1 and MAP2K1 blocked both PDGF-and E2-induced gonocyte proliferation, placing these factors downstream in the pathways (Thuillier et al, 2010). Interestingly, E2 did not promote cycling in gonocytes in the absence of PDGF, highlighting its dependence.…”
Section: Ink4bmentioning
confidence: 99%